Los sistemas de almacenamiento inka de Tambo Viejo - Valdez, Lidio M.; Bettcher, Katrina J. (Pontificia Universidad Católica del Perú, 2025)
The Inka State built enormous dispersed warehouses throughout their empire in order to store all types of goods. These facilities were built in clusters, usually atop mountain summits, and seem to suggest that Inka storage systems were always of enormous size. Yet recent archaeological research suggests that smaller scale warehouses, different from those found in the Peruvian highlands, were also erected on the coastlands. This paper examines the cists of Tambo Viejo semisubterranean facilities of varying shape that were also used as storehouses, as follows from the discovery made inside them of items such as maize kernels and coca leaves. This find shows that other forms of storage that probably preceded the development of the State were in place during the Inka expansion on the southern coast of Peru. Just like in the highlands, these forms of storage took advantage of coast’s environmental characteristics in order to attain an efficient preservation of food.

El Estado inka construyó enormes depósitos dispersos a lo largo del imperio para almacenar todo tipo de productos. Estas instalaciones, edificadas en grupos y, por lo general, en la cima de los cerros, podrían sugerir que los sistemas de almacenamiento inka siempre fueron enormes. Sin embargo, recientes investigaciones arqueológicas demuestran que en la costa también existieron depósitos, pero de menor escala, distintos de los que suelen encontrarse en la sierra peruana. Este artículo trata sobre las cistas de Tambo Viejo, instalaciones semisubterráneas de formas variadas que, a juzgar por el hallazgo de productos como granos de maíz y hojas de coca en su interior, también habrían funcionado como almacenes. Este descubrimiento demuestra que durante la expansión inka hacia la costa sur existieron formas de almacenamiento que posiblemente precedieron al desarrollo del Estado y que aprovecharon las características medioambientales de la zona para lograr una conservación eficiente de alimentos, tal como sucedió en la sierra.
Inka storage systems at Tambo Viejo
Keywords: Inka state; Storage; Tambo Viejo; South coast; Maize; Coca leaves; Estado inka; Almacenamiento; Tambo Viejo; Costa sur; Maíz; Hojas de coca; https://purl.org/pe-repo/ocde/ford#6.01.02